Three questions to ask before using model outputs for decision support - Grimm, Volker; Johnston, Alice S. A.; Thulke, H.-H.; Forbes, V. E.; Thorbek, P. (Nature Publishing Group, 2020)
Decision makers must have sufficient confidence in models if they are to influence their decisions. We propose three screening questions to critically evaluate models with respect to their purpose, organization, and evidence. They enable a more transparent, robust, and secure use of model outputs.